2021
DOI: 10.1007/978-3-030-83823-2_45
|View full text |Cite
|
Sign up to set email alerts
|

Building a Larger Class of Graphs for Efficient Reconfiguration of Vertex Colouring

Abstract: A k-colouring of a graph G is an assignment of at most k colours to the vertices of G so that adjacent vertices are assigned different colours. The reconfiguration graph of the k-colourings, R k (G), is the graph whose vertices are the k-colourings of G and two colourings are joined by an edge in R k (G) if they differ in colour on exactly one vertex. For a k-colourable graph G, we investigate the connectivity and diameter of R k+1 (G). It is known that not all weakly chordal graphs have the property that R k+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…They also showed that every 3colourable (P 5 , co-P 5 , C 5 )-free graph is ℓ-mixing and the ℓ-recolouring diameter is at most 2n 2 [7]. Biedl, Lubiw, and Merkel [1] showed that every P 4 -sparse graph is ℓ-mixing and the ℓrecolouring diameter is at most 4n 2 . The last author [11] showed that for all p ≥ 1, there exists a k-colourable weakly chordal graph that is not (k + p)-mixing.…”
Section: Theorem 2 ([8]mentioning
confidence: 99%
See 1 more Smart Citation
“…They also showed that every 3colourable (P 5 , co-P 5 , C 5 )-free graph is ℓ-mixing and the ℓ-recolouring diameter is at most 2n 2 [7]. Biedl, Lubiw, and Merkel [1] showed that every P 4 -sparse graph is ℓ-mixing and the ℓrecolouring diameter is at most 4n 2 . The last author [11] showed that for all p ≥ 1, there exists a k-colourable weakly chordal graph that is not (k + p)-mixing.…”
Section: Theorem 2 ([8]mentioning
confidence: 99%
“…There are 11 graphs on 4 vertices (see Figure 1). Bonamy and Bousquet [3] showed that every P 4 -free graph G is ℓ-mixing and the ℓ-recolouring diameter is at most 2 • χ(G) • n. Biedl, Lubiw, and Merkel [1] investigated a class of graphs that generalizes P 4 -free graphs. The following theorem was not directly stated in [1] but follows from the proof of Theorem 1 in [1] and improves the bound on the ℓ-recolouring diameter of a P 4 -free graph.…”
mentioning
confidence: 99%